Pengaruh Lingkungan Sekolah terhadap Kejenuhan Belajar serta Implikasinya pada Hasil Belajar Siswa Mata Pelajaran Ekonomi - Prawesty, Novia Nissya; Afriza, Edi Fitriana; Aisyah, Iis (Civiliza Publishing, Indonesia., 2023)
The study was carried out in response to the issues at MAN 3 Tasikmalaya, namely the poor learning results. This was shown by several students who failed to meet the minimal completion standard (KKM) for economics courses. Education quality may suffer as a consequence of poor student learning results. This study's goal was to ascertain how the school setting affected learning saturation and what it meant for students' performance in economics courses. This study used an explanatory survey together with questionnaires and methods for data gathering from observation. 136 class XII IPS students make up the population, which was selected using a saturated sample. approaches for data analysis that use route analysis. The findings of the study indicate that: 1). The school setting has a negatif and substantial impact on students' learning saturation in economics courses, 2). The learning results of students in economics topics are positively and significantly impacted by the school environment, 3). Student learning results in economics disciplines are negatifly and significantly impacted by school learning saturation, 4). Through learning saturation, the school setting has a substantial impact on students' economics learning results.